Folate Analysis in Ancient Wheat Variety: A Comprehensive Review of Factors Impacting - Purbia, Nikita; Meena, Dr. Sumitra; Yadav, Sakshi R (Annals of Arid Zone, 2025)
This comprehensive review explores the nutritional significance of ancient wheat varieties, including spelt, einkorn, emmer, and Khorasan wheat, focusing on their folate content. Wheat, a fundamental cereal grain, plays a crucial role in global diets. Despite claims about the high folic acid content in ancient wheat, there is limited research to substantiate these assertions. The review systematically compares folate levels in ancient wheat varieties, highlighting the scarcity of data in this domain. Factors influencing folate content, such as geographic and genetic variations, processing, milling, fermentation, germination, and storage, are extensively examined. The study emphasizes the potential health benefits of consuming folate-enriched ancient wheat, addressing deficiencies and offering practical strategies like crop fortification. Additionally, it discusses dietary recommendations for folate intake in India. The methodology section details challenges in folate quantification, utilizing microbiological assay and high-performance liquid chromatography. In conclusion, this review calls for a renewed focus on the exploration and validation of the nutritional profile of ancient wheat varieties, emphasizing their potential to contribute significantly to improved dietary folate intake and public health